DESAIN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM TERPUSAT PADA SISWA - Muhammad Izudin Ardani; Tasman Hamami (Raudhah - Proud To Be Professional, 2023)
Abstract The purpose of this research is to find out how to design a student-centered curriculum, its principles, advantages and disadvantages. This research uses a qualitative method, the type of method used is library research. The results of this study are that there are 3 designs and developments, centered curriculum designs are divided into 3 namely alternative school designs, humanistic designs and activities and experience centered designs. An alternative design in PAI learning using a student-centered curriculum design can be done by running a problem solving system. For example, students are invited to discuss solving moral problems about anger. The use of humanistic design in PAI learning in a student-centered design can be used by dividing students based on the students' interests in the focus of PAI learning materials. The teacher teaches the material and gives discussion assignments. design is centered on experience which is difficult to apply not only in PAI subjects but in almost all subjects. The most important of these designs, students must want the material itself. Educators must teach each student with a focus on the material each student chooses and likes.